PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS VISUAL UNTUK PESERTA DIDIK TUNARUNGU - Weluk, Kristina; Leton, Samuel; Lakapu, Meryani (Journal of Honai Math, 2020)
Students who have special needs also have the right to obtain an education as a provision for life, just like regular students. However, several learning tools for them are still very few. It is because some researchers always focus on standard students. Therefore, this study aims to develop visual-based mathematics teaching materials on integer arithmetic operations, one of which is deaf students. The development model used is a modified development model from the 4D model. Teaching materials that have been developed and tested on deaf class VIII students are suitable for use as a learning medium because they meet the criteria of being valid, practical, and effective. Valid because the average value of the three validators is 3.85. Furthermore, the practical standard is because the percentage of the average response score of students obtained is 80%. Finally, the effective criterion is that the average score of students trying to solve the test questions is 81. The results of this study contribute to providing alternative teaching materials for deaf students.